PENGARUH LATIHAN FARTLEK TERHADAP DAYA TAHAN VO2 MAX PADA TIM BOLA BASKET SMAN 8 PEKANABARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this research is that when athletes are training or participating in competitions, it is clear that the quarter 1-2 is very good, and during the 3-4 quarters it is very lacking, the purpose of this research is to to determine the athlete's stamina. The form of this research is (one group pretest-postest design) with the population of the SMA Negeri 8 Pekanbaru basketball team. The data in this research is a population of 9 people. The instrument used in this research was a sleep test, which aims to determine the effect of fartlek training. Based on the analysis of the normality test on the independent variable (X), it produces a LoMax of 0.131 and an L table of 0.271, which means that LoMax <L table. The dependent variable (Y) returns a LoMax of 0.142 and an L table of 0.271. This means that LoMax <L The data table is normally distributed. In the t-distribution hypothesis, it can be tested that the variable between x and the variable y is obtained by the value of t = 6.812, then tcount> ttable, namely (6.812)> (1.860), then Ha is accepted, with in other words, there is an effect of fartlektraining on the vo2max endurance of the SMAN 8 Pekanabaru basketball team.Key Words: Fartlek Training, Vo2Maks Endurance, Basketball